The modern State and the protestant Reform from Quentin Skinner’s Interpretation - Jusviack, Patrícia; Westphal, Euler Renato (Vox Scripturae - Revista Teológica Internacional, 2016)
The text shows the different movements that before Luther had already taken about the same theological premises and also these movements questioned the overindulgence of the Catholic Church.  Linked to these ideas, Luther developed a theory that revoked any church authority to control the worldly matters or spiritual frameworks. The task of the church is only to guide the believers. Luther posited that the secular government put his power on the worldly context. He told about the possibility to the pacific resistance against the tyrant ruling. The ecclesiastic authority couldn’t provide Power on the secular authority. The liberty of the conscience from the justification by grace and by faith provided the base of the political liberty, freedom and the equality. The political and economic liberal theories have their theoretical foundation in the protestant Reformation. The France Revolution gave up the protestant fundamentation and became an intolerant regime of wars and executions. The culture and the cultural heritage of the Reformation to proportionate the process of the modern secularization. This article had as base the discussion about the theme of politic from Quentin Skinner in dialog with Luther and contemporaries theorists.
Keywords: Secularization; Theory of the State; Protestantism; Immaterial Cultural Heritage